Clampless cardioplegia: an alternative to conventional cardioplegia administration. (July 2019) - Clingan, Sean; Reagor, James
Myocardial protection is of the utmost importance during cardiac surgery. At times, there are patients who present to the operating room who make the typical use of cardioplegia difficult or impossible. For these patients, a separate protocol and process must be in place. "Clampless cardioplegia" is an option when the ascending aorta cannot be cross-clamped, but the surgeon needs a bloodless field with a quiescent heart. This study reports on the process of developing a policy and protocol for utilizing clampless or systemic cardioplegia. Four case reports of patients who received clampless or systemic cardioplegia and their peri-operative courses are described. These four patients showed no cardiac functional change by post-operative echocardiogram and no peri-operative complications are reported.